INCREASED ALL-CAUSE MORTALITY, TOTAL CARDIOVASCULAR DISEASE AND MORBIDITY IN HOSPITALIZED OCTOGENARIANS WITH ORTHOSTATIC HYPOTENSION. (June 2018) - Lindstedt, I.; Edvinsson, L.; Lindberg, A.L.; Olsson, M.; Dahlgren, C.; Edvinsson, M.L.
Abstract : Objective: Orthostatic hypotension is a common finding in elderly patients and is associated with significant morbidity and mortality. Most of the knowledge on orthostatic hypotension and cardiovascular endpoints and mortality comes from prospective cohort data and there are few clinical studies performed in octogenarians. Design and method: From the year 2014 until May of the year 2017 a team composed of a physiotherapist and an occupational therapist supervised by a medical doctor visited newly hospitalized patients at Lund's University Hospital. The team measured BMI, blood pressure, pulse, saturation and registered the patients' age, sex, number and types of medications and symptoms for admittance. They were also able to register blood tests taken, the patients' final diagnosis, the number of days in hospital, the number of medications at discharge, the number of re-hospitalizations and the number of deaths at follow-up after 6 months. Patients with complete blood pressure measurements both in the lying position and standing position were included in our study (n = 210). These patients were divided into two groups, the orthostatic hypotension group (n = 119) and the normotensive group (n = 91). Mean age was 83 years. Results: During follow-up 14 of 91 patients died in the normotensive group compared to 32 of 119 in the orthostatic hypotension group (p < 0, 05). At discharge 41 of 91 patient had been diagnosed with cardiovascular disease in the normotensive group compared to 70 of 119 patients in the orthostatic hypotension group (p < 0, 05). The patients in the normotensive group stayed at the hospital for a mean of 8, 38 days compared to the patients from the orthostatic hypotension group whom stayed for a mean of 9, 86 days (p < 0, 05). Conclusions: This study has shown that there is increased cardiovascular disease, morbidity and mortality in elderly patients with orthostatic hypotension compared to patients without orthostatic hypotension in a hospital setting. The study results indicate the importance of taking orthostatic blood pressure tests in elderly patients.